2005
DOI: 10.1007/s11095-005-5272-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel in Vitro and Numerical Analysis of Shear-Induced Drug Release from Extended-Release Tablets in the Fed Stomach

Abstract: Shear force effects on drug release from matrix tablets relevant for fed state are for the first time possible to predict by in vitro dissolution testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 17 publications
5
94
0
Order By: Relevance
“…Periodically generated ACWs induce the motion of the gastric contents, mix the gastric contents, and grind bulk solid foods to reduce their particle size (Kong and Singh, 2008). Several research groups have reported that fluid motions in the stomach promote the emulsification of oil components and drug release from matrix tablets (Schwizer et al, 2006;Abrahamsson et al, 2005). Ajaj et al (2004) reported unusual peristaltic motions in gastroparesis patients having a decreased ACW speed or different degrees of ACW contractions, which were monitored by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…Periodically generated ACWs induce the motion of the gastric contents, mix the gastric contents, and grind bulk solid foods to reduce their particle size (Kong and Singh, 2008). Several research groups have reported that fluid motions in the stomach promote the emulsification of oil components and drug release from matrix tablets (Schwizer et al, 2006;Abrahamsson et al, 2005). Ajaj et al (2004) reported unusual peristaltic motions in gastroparesis patients having a decreased ACW speed or different degrees of ACW contractions, which were monitored by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic conditions generated in a USP II apparatus can be compared to the expected in vivo hydrodynamics by using the Reynolds number and the Reynolds numbers for bulk flow in the USP II apparatus are around 2000 [141] which is significantly greater than the physiological range (0.1 -30) as suggested by Abrahamsson et al [51,140].…”
Section: Dissolution Apparatusesmentioning
confidence: 99%
“…Viscosity is also affected by pH in addition to soluble meal content and concentration [4]. Test meals containing dietary fibres are administered that have viscosities ranging from 10 to > 10,000 cP [4,48,49] [4,50,51].…”
Section: Physiological Parametersmentioning
confidence: 99%
See 2 more Smart Citations